2020
DOI: 10.1371/journal.pone.0239233
|View full text |Cite
|
Sign up to set email alerts
|

The influence of topical non-steroidal anti-inflammatory drugs on the intraocular pressure lowering effect of topical prostaglandin analogues—A systemic review and meta-analysis

Abstract: Purpose This study aimed to review previous articles and evaluate the influence of topical non-steroidal anti-inflammatory drugs (NSAIDs) on intraocular pressure (IOP) in glaucoma patients who were treated with prostaglandin analogues (PGs). Method The presenting study was designed as a meta-analysis of previous research. Databases include PubMed, Web of science, Cochrane library, and Embase were searched with keywords of “intraocular pressure, prostaglandin analogues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This was a rather surprising finding considering the meta-analysis by Lo et al who suggested an enhanced IOP-lowering effect of combined NSAID and PGA administration. It should be noted that the meta-analysis did not address their perioperative use [ 23 ]. Fakhraie et al reported similar IOP values between groups regardless of latanoprost continuation until the 3rd postoperative month [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a rather surprising finding considering the meta-analysis by Lo et al who suggested an enhanced IOP-lowering effect of combined NSAID and PGA administration. It should be noted that the meta-analysis did not address their perioperative use [ 23 ]. Fakhraie et al reported similar IOP values between groups regardless of latanoprost continuation until the 3rd postoperative month [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another point of clinical interest that few studies have examined is the efficacy of postoperative PGA use, particularly with concomitant topical NSAID administration. The meta-analysis by Lo et al reportedincreased hypotensive action of PGAs when concomitantly administered with NSAIDs, but this has not been comprehensively evaluated in a postoperative setting [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the usage of topical NSAIDs may enhance the lowering of IOP from topical prostaglandin analog treatment for glaucoma patients, the usage of NSAIDs with glaucoma filtration surgery remains controversial [ 107 ]. Clinically, NSAIDs are not routinely used after glaucoma filtration surgery.…”
Section: Strategies To Prevent Ocular Fibrosis Following Glaucoma Fil...mentioning
confidence: 99%
“…Recent data have pinpointed potentially interesting routes to mediate glaucomatous RGC dysfunction [ 9 ]. Meanwhile, hypotensive therapy (medical, laser, surgical) is the only way to fight against the elevated IOP [ 10 , 11 ]. Despite experimental advances in neuroprotection [ 12 , 13 , 14 ], there is no definitive cure for glaucoma ND.…”
Section: Introductionmentioning
confidence: 99%